Defining an Adequate Sample of Earlywood Vessels for Retrospective Injury Detection in Diffuse-Porous Species - Arbellay, Estelle; Corona, Christophe; Stoffel, Markus; Fonti, Patrick; Decaulne, Armelle (PLoS ONE, 2012)
International audience Vessels of broad-leaved trees have been analyzed to study how trees deal with various environmental factors. Cambialinjury, in particular, has been reported to induce the formation of narrower conduits. Yet, little or no effort has beendevoted to the elaboration of vessel sampling strategies for retrospective injury detection based on vessel lumen sizereduction. To fill this methodological gap, four wounded individuals each of grey alder (Alnus incana (L.) Moench) anddowny birch (Betula pubescens Ehrh.) were harvested in an avalanche path. Earlywood vessel lumina were measured andcompared for each tree between the injury ring built during the growing season following wounding and the control ringlaid down the previous year. Measurements were performed along a 10 mm wide radial strip, located directly next to theinjury. Specifically, this study aimed at (i) investigating the intra-annual duration and local extension of vessel narrowingclose to the wound margin and (ii) identifying an adequate sample of earlywood vessels (number and intra-ring location ofcells) attesting to cambial injury. Based on the results of this study, we recommend analyzing at least 30 vessels in each ring.Within the 10 mm wide segment of the injury ring, wound-induced reduction in vessel lumen size did not fade withincreasing radial and tangential distances, but we nevertheless advise favoring early earlywood vessels located closest tothe injury. These findings, derived from two species widespread across subarctic, mountainous, and temperate regions, willassist retrospective injury detection in Alnus, Betula, and other diffuse-porous species as well as future related research onhydraulic implications after wounding.